Time reduction of mudmee silk yarn manufacturing in the Khon-Mee process at the community level in Thailand - Haanchumpol, Thidathip; Sermpongpan, Chatchai; Jaiprasit, Vachirawich; Phiboonsiri, Pongsatorn; Talumpuk, Nithikorn (Engineering and Applied Science Research, 2023)
This research is aimed to reduce the average time spent on solving the delay in the Khon-Mee process that causes the delivery of silk yarn to customers to take longer than planned. The cause is broken yarn during manufacturing and the inability to stop the Khon-Mee machine immediately. The researcher created the broken yarn detector device, a new device at the community level; when detecting broken yarn, the light was turned on to show the Khon-Mee process status was stopped. Then the operator connected the silk yarn to continue to run the machine until finished. The results showed the average time spent on solving that problem decreased from 132.90 minutes to 67.85 minutes, and the time savings achieved as 65.05 minutes accounted for 48.95%. Maximum weekly productivity increased from 216 sets to 360 sets, and the productivity was accreted as 144 sets accounted for 66.67%. Consequently, the sufficient silk yarn for the required customer is 250 sets per week.